PENATAAN PENGISIAN JABATAN KEPALA KEPOLISIAN REPUBLIK INDONESIA DALAM SISTEM KETATANEGARAAN DI INDONESIA - Muhammad Jimmy Waldani; Dessy Artina; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
In the amendments to the 1945 Constitution, there are several balances ofpower in the relationship between the President and state institutions. This isdone as a reduction in the power of the President which has been seen as a verylarge prerogative in running the state administration system in Indonesia. Thischange is based on considerations to improve the efficiency and effectiveness ofstate administration. If we look closely, regarding the systematics of theappointment of the National Police Chief, it is worth asking about the location ofthe President's prerogative in the appointment of the National Police Chief. ThePresident's prerogative is a privilege possessed by the President to do somethingwithout seeking approval from other institutions. The purpose of writing thisthesis: First, to find out the problems in filling the position of the Chief of theIndonesian National Police with the approval of the DPR. Second, to find out theconcept of realigning the filling of the position of the Chief of the IndonesianNational Police in the constitutional system in Indonesia.The type of research used in this legal research is normative legalresearch. the approach used by the researcher is a normative juridical approach.Analysis of the data used is the author analyzes the data qualitatively. In drawingconclusions, the author uses the deductive method of thinking, namely a way ofthinking that draws conclusions from a general statement or proposition into aspecific statement.From the research results, there are two main things that can beconcluded. First, regarding the issue of filling the position of Chief of Police ofthe Republic of Indonesia with the approval of the DPR, it is divided into twopoints, including: (1) this seems to violate the concept of prerogative rights ownedby the President, (2) has the potential to create conflicts regarding decisionsmade between the DPR and the President. . Second, regarding the concept ofrealigning the filling of the position of the Chief of the Police of the Republic ofIndonesia in the constitutional system in Indonesia, it is divided into two points,including: (1) by strengthening the prerogative rights of the President, (2)promoting the concept of Check and Balances.Keywords: Prerogative Rights – State Administration System – President andDPR